Application of continuous improvement process in reducing the return-cleaning rate of lumen surgical instruments (质量持续改进活动在降低手术管腔器械清洗返洗率中的应用) - JIANG Linghua (蒋玲华); LI Shaoping (李绍平); YAO Shixiu (姚仕秀); YANG Weizao (杨伟造) (中西医结合护理)
Objective To investigate the effect of continuous improvement process (CIP) in reducing the return-cleaning rate of lumen surgical instruments. Methods A CIP group was set up, and theme and plan of CIP activities were identified. The current situation of lumen surgical instruments cleaning was investigated, and existing problems and potential risk factors were analyzed. Targeted strategies were carried out by a PDCA circle and implementation effect was evaluated. The return-cleaning rate of 846 pieces of lumen surgical instruments selected before implementation of CIP activities and 846 pieces selected after implementation of CIP activities was compared. Results The return-cleaning rate dropped from11. 11%(94/846)before implementation of CIP activities to 4. 37%(37/846)after implementation of CIP activities, with a significant difference (P＜0. 01). Conclusion Application of CIP is potentially effective to improve the quality of lumen surgical instruments cleaning and working efficacy in the central sterile supply department. (目的 探索质量持续改进(CIP)活动项目在降低手术管腔器械清洗返洗率中的应用效果。方法 成立CIP活动小组, 首先选定主题, 拟定活动项目计划书、调查工作现况、对目标值进行设定, 然后分析目前存在的问题和主要原因, 并针对真因拟定具体对策, 通过PDCA循环实施对策并评价实施效果, 最后进行本次活动的检讨与改进。分析CIP活动前后各846件手术管腔器械清洗质量, 比较开展CIP活动前后手术管腔器械清洗的返洗率。结果 手术管腔器械返洗率由CIP活动前的11. 11%(94/846)降低至CIP活动后4. 37%(37/846), 差异有统计学意义(P＜0. 01)。结论 将CIP活动应用到消毒供应中心手术管腔器械清洗质量管理中效果明显, 即能有效提高手术管腔器械的清洗质量, 又能提高工作效率。)